Control reconfiguration strategies for Remaining Useful Life extension. Issue 34 (2022) - Thuillier, J.; Jha, M.S.; Galeotta, M.; Theilliol, D.
Abstract: Extending the Remaining Useful Life (RUL) of dynamic systems functioning in closed loop in accordance with damage progression dynamics is a challenging task. Such target combines the challenges emanating from the domain of Prognostic Health Management (PHM) and engineering of the control theory. The main contribution of the paper consists in the synthesis and the analysis of two control reconfiguration strategies in order to achieve such objective. This paper presents two control strategies, one reconfigures the controls input and the other reconfigures the setpoint. The first structure modifies the controls input sent to the system using a modulation parameter. The second structure proposes a modification to the operational setpoint of the system's control loop. These modulations are obtained from an optimization algorithm making it possible to achieve a trade-off between the dynamic performance requirement and the RUL criteria. The optimization algorithm is based on the prediction of the RUL and on the estimation of the deterioration. A numerical example illustrates the use of each of these two strategies, through the results of estimating the deterioration, predicting RUL, and obtaining the modulation parameter from the optimization. The RUL extension and its impact on performance trade-off are illustrated to evaluate the performances of both strategies.